Comparison of global left ventricular myocardial work indices at baseline and after 3 months of st-segment elevation myocardial infarction. (25th November 2020) - De Paula Lustosa, R; Van Der Bijl, P; Goedemans, L; El Mahdiui, M; Montero-Cabezas, J.M; Kostyukevich, M; Ajmone Marsan, N; Bax, J.J; Delgado, V
Abstract: Background: Global left ventricular myocardial work indices (GLVMWI) are derived from speckle tracking echocardiographic strain data in combination with non-invasive blood pressure recordings. Global work index (GWI), global constructive work (GCW), global wasted work (GWW) and global work efficiency (GWE) are derived from these measures. GLVMWI in ST-segment elevation myocardial infarction (STEMI) remains unexplored and comparison between measures of GLVMWI at index event (baseline) and follow-up is unknown. Purpose: To assess the evolution in GLVMWI in STEMI patients from baseline (index infarct) to 3 months' follow-up. Methods: This retrospective study included 350 patients (265 men, mean age: 61±10 years) with STEMI treated with primary percutaneous coronary intervention and optimal, guideline-based medical therapy. Clinical variables, echocardiographic measures and GLVMWI were recorded at baseline and 3 months follow-up. Results: Left ventricular ejection fraction (LVEF), global longitudinal strain (GLS), GWI, GCW and GWE improved significantly at 3 months follow-up with no significant difference in GWW (Table). These findings suggest that the impaired values of GLVMWI at baseline are related to stunning after STEMI and they recover at 3 months follow-up without further deterioration in GWW, which probably reflects irreversible myocardial damage. Conclusions: In STEMI patients treated with primary percutaneous coronary intervention and optimal guideline-based medical therapy, GLVMWI assessed by speckle tracking strain echocardiography are significantly improved at 3 months follow-up, without significant changes in GWW. GLVMWI therefore have the potential to identify reversible and irreversible components of post-infarct myocardial damage. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): European Society of Cardiology Research Grant